Professional Care Networks of Frail Older People: An Explorative Survey Study from the Patient Perspective - Grol, Sietske M. (Int J Integr Care, 2020)
BACKGROUND: Frail older people living in the community require multidisciplinary care. Despite the fact that patient participation is high on the public agenda, studies into multidisciplinary care mainly focus on the viewpoints of professionals. Little is known about frail older patients’ experiences with care delivered by multidisciplinary teams and their perception of collaboration between professional and informal caregivers. OBJECTIVE: To gain more insight into the experiences of frail older patients with integrated multidisciplinary care by mapping the care networks of this patient group and their perception of the interconnection between professional and informal caregivers. METHODS: Survey study to facilitate a care network analysis. Due to the vulnerable health status of the respondents, questionnaires were completed during interviews. Analysis was performed using an iterative process, using both visual and metric techniques. PARTICIPANTS: 44 older persons, considered ‘frail’ by their general practitioner. SETTING: Four general practices in The Netherlands. RESULTS: The networks of the participants consisted of an average of 15 actors connected by 54 ties. General practitioners were the most common actors in the networks, and were well connected to medical specialists and in-home care providers. The participants did not always perceive a connection between their general practitioner and their informal caregiver. The network analyses resulted in the identification of three subtypes: simple star (n = 16), complex star (n = 16), and sub-group networks (n = 12). CONCLUSIONS: Our findings indicate that the elderly often do not experience the integration of multidisciplinary care as such. This is a real opportunity for MTs to improve their care and to make the patients’ experiences better in line with what they are aiming: allowing patients to live at home as healthy and independently as possible for as long as possible. We showed that informal caregivers often form communication bridges between patients and professionals. Having a better knowledge of the patient perspective enables the gaps in professional care networks of frail older people to be filled and facilitates the anticipation of crisis situations.